2010
DOI: 10.1007/s12291-010-0090-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metformin on Hormonal and Biochemical Profile in PCOS Before and After Therapy

Abstract: Insulin resistance and the resultant hyperinsulinemia exacerbate the reproductive abnormalities of Polycystic Ovarian Syndrome by increasing ovarian androgen productions and decreasing serum sex hormone binding globulin. The present study was conducted to estimate serum insulin and testosterone level in 44 PCOS cases and 32 control patients. Simultaneously the role of metformin (an insulin sensitizing agent) in modulating insulin resistance and serum androgen level was also analyzed. A significant rise in seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
(30 reference statements)
2
9
0
2
Order By: Relevance
“…15 The hormones show a rise of serum insulin and testosterone in PCOS cases when compared to control (p<0.001), indicating the role of hyperinsulinemia in the pathogenesis of PCOS. 16,17 A significantly higher (p<0.001) mean PSA levels of cases were observed than the control group which was in similar with the observations of Melegos et al and Gullu et al, confirming that PCOS, a hyperandrogenemic disease is likely to be present with high levels of PSA. 18,19 Taking the fasting glucose to insulin ratio of ≤4.5 as insulin resistance, 62% of cases and 8.3% of controls were considered as insulin resistant.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…15 The hormones show a rise of serum insulin and testosterone in PCOS cases when compared to control (p<0.001), indicating the role of hyperinsulinemia in the pathogenesis of PCOS. 16,17 A significantly higher (p<0.001) mean PSA levels of cases were observed than the control group which was in similar with the observations of Melegos et al and Gullu et al, confirming that PCOS, a hyperandrogenemic disease is likely to be present with high levels of PSA. 18,19 Taking the fasting glucose to insulin ratio of ≤4.5 as insulin resistance, 62% of cases and 8.3% of controls were considered as insulin resistant.…”
Section: Resultssupporting
confidence: 88%
“…22 Insulin resistance also reduced from 75.62% of cases to 42.3% after therapy, which was in concurrence with the studies that metformin exert its effects by encouraging peripheral glucose utilisation. 16,23 When we studied the effect of metformin on PSA level, no significant change was observed in our group of patients. Jonathan L, et al demonstrated a decrease in PSA level in their group of prostate cancer patients after metformin therapy.…”
Section: Resultsmentioning
confidence: 66%
“…Affecting up to 75% of PCOS patients (29), HA may be the major factor in development of IR in PCOS patients. A positive correlation between serum testosterone level and insulin level has been observed in women with PCOS (37). Insulin resistance was associated with decreased basal metabolic rate in women with PCOS and HA (38).…”
Section: Discussionmentioning
confidence: 94%
“…Our study showed that, non-obese PCOS patients presented with increased body iron stores and a marked increase in hormones insulin and testosterone which are in agreement with other workers. [13][14][15][16] Marked rise in serum total testosterone in these cases may be due to excess ovarian production of androgens, which is central to the diagnosis of PCOS. 17 Yet some researchers have shown apparently normal testosterone concentrations in their PCOS cases, which may be attributed to their low to normal sex hormone binding globulin levels.…”
Section: Associations Between Ferritin and Hormonesmentioning
confidence: 99%